Intervención psicológica y salud mental en personas que han sufrido desastres naturales. - Parra Galarza, Angie Maday (2024)
Psychological intervention follows an important process after traumatic events that generate an emotional imbalance, therefore, the objective is focused on the effects of mental health and intervention towards victims of natural disasters, in addition to the description of methods and the effectiveness they generate. This research is bibliographic and descriptive, which is based on the review of scientific research, with a sample of 38 articles from a non-probabilistic sampling, which have been evaluated by a qualification process with a methodological quality matrix of Critical Review Form-Quantitive Studies (CRF-QS). Results show the repercussions on mental health that have been caused by these catastrophic events such as anxiety, depression, acute stress, post-traumatic stress, and sleep disorders, among others; In addition, positive effects are identified on many subjects, such as Post-Traumatic Growth, Resilience, Social Well-being, Sense of Community, etc. In the interventions carried out, the effectiveness of Cognitive Therapy, Cognitive Behavioral Therapy, Group Therapy, Play Therapy, and Acceptance and Commitment Therapy is sometimes demonstrated. These results allow us to infer the negative consequences at a psychological level caused by the stressful event and it is evident, in all psychological approaches, they allow us to contrast the evaluation of the previous symptoms in the affected subjects after the intervention, within this, they have managed positive results in reducing symptoms.